EFEKTIFAS PEMINDAI TERMAL UNTUK MENDETEKSI COVID-19 : Effectiveness of Thermal Scanner for Detecting Covid-19 - Siti Nurfadilah H.; Ardiansyah Pandayu (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
Infrared thermal inspection through the use of thermal scanners, has been widely implemented throughout the world. This research aims to analyze the effectiveness of thermal scanners in detecting Covid-19. The research was conducted using a cross-sectional research design with a retrospective approach. This research was conducted in the period January-June 2021. The sample in this study was taken from the total population. Where the number of research subjects is all samples that have met the inclusion and exclusion criteria. The research results show that a high positive likelihood ratio of 15 means that individuals who are confirmed positive for COVID-19 are 15 times more likely to experience fever (temperature above 37.5˚C) than healthy individuals. This implies that a positive thermal scanner is a significant indicator of a confirmed positive SARS CoV-2 test result. Thermal scanners have good sensitivity and specificity in detecting body temperature. Even though there is a decrease in the sensitivity of thermal scanners in a pandemic situation, this research shows that the use of thermal scanners is a crucial effort in detecting body temperature when the virus is transmitted to the majority of the population.